Potential of Favipiravir Analogs as SARS-CoV-2 RdRp Inhibitors: Synthesis and In Silico Studies - Alni, Anita; Lokitha, Angela; Maulana, Yusuf Eka; Hermawati, Elvira; Danova, Ade (Indonesian Journal of Chemistry, 2026)
The novel severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is responsible for causing the lethal infectious disease known as COVID-19. The RNA-dependent RNA polymerase (RdRp) is a pivotal component that facilitates the translation of viral RNA into viral proteins. Therefore, our study aimed to synthesize new inhibitors from favipiravir (FVP) analogs by modifying the hydrophobicity through a nucleophilic aromatic substitution at the C-6 position of the pyrazine ring with alkoxy groups under acidic conditions. Moreover, the synthesized FVP analogs were investigated for their antiviral potency against SARS-CoV-2 RdRp through in silico studies. Five FVP analogs (3–7), including four known (3, 4, 5, 7) and one new (6), were successfully synthesized with yields ranging from 2.3 to 32.7%. All favipiravir analogs could be drug-likeness with inactive hepatotoxicity and carcinogenicity. The docking study showed that compound 5 exhibited a strong binding affinity with a binding score of −7.00 kcal/mol by interacting with the catalytic site residues of Asp618 and Asp760 of SARS-CoV-2 RdRp. Furthermore, the molecular dynamics simulation revealed that the compound 5 was stable, as indicated by RMSD, Rg, solute H-bonds, RMSF, and binding energy calculations. Thus, these results suggest that the FVP-RTP analog (5) may have antiviral potency by targeting SARS-CoV-2 RdRp.